Coffee Culture and Mental Well-being: A Comparative Study of Modern and Traditional Coffeeshops in Al Qassim - Maspul, Kurniawan Arif (Journal of Advanced Health Informatics Research, 2024)
This study looks into the effects of modern and traditional coffeeshops on the mental health of customers in the Saudi Arabian province of Al Qassim, with a focus on the cities of Buraydah and Unaizah. The proliferation of diverse coffeeshop kinds has resulted in the emergence of each giving a distinct experience and atmosphere. Understanding the impact of different coffee shop types on mental well-being is critical for the creation of long-lasting and prosperous coffee communities in Al Qassim. The study addresses five major concerns: the impact of coffee shops on consumers' sense of autonomy and empowerment, the impact of environmental stimuli on psychological well-being, the role of quality and satisfaction in shaping coffee shop experiences, strategies for bridging the gap between modern and traditional coffeeshops. To gain insights, a thorough research technique was used, which included a qualitative literature review, talks, and observations. The findings emphasize the considerable impact of modern and traditional coffeeshops on mental health, underlining the necessity of collaboration and sustainability in cultivating an inclusive coffee culture that improves the well-being of the Al Qassim society.